2020
DOI: 10.1089/jmf.2018.4357
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus Granules Dose-Dependently Balance Intestinal Microbiome Disorders and Ameliorate Chronic Alcohol-Induced Liver Injury

Abstract: As the functions of Lactobacilli become better understood, there are increasing numbers of applications for Lactobacillus products. Previously, we have demonstrated that Lactobacillus rhamnosus GG (LGG) can prevent alcoholic liver injury. LGG granules were produced by fluid bed granulation with a media composed of starch, skimmed milk powder, whey powder, microcrystalline cellulose and maltose, and LGG fermented liquid that comprised 30-50% of the total weight. We found LGG granules dose-dependently protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…However, the L. salivarius Li01 intervention changed the structure of the gut microbiota and increased the relative abundance of Lactobacillus. The TAA injection favoured Proteobacteria and Helicobacter, which include many pathogens, have been related to liver injury in a previous study (Gu et al, 2020), and were positively correlated with systematic inflammation in our study. However, the L. salivarius Li01 pretreatment reduced these bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…However, the L. salivarius Li01 intervention changed the structure of the gut microbiota and increased the relative abundance of Lactobacillus. The TAA injection favoured Proteobacteria and Helicobacter, which include many pathogens, have been related to liver injury in a previous study (Gu et al, 2020), and were positively correlated with systematic inflammation in our study. However, the L. salivarius Li01 pretreatment reduced these bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we observed that alcohol consumption increased Prevotella and Parasutterella and decreased Clostridium , Turcibacter and Romboutsia , which is in line with the previous reports [ 46 , 47 , 48 , 49 ]. Moreover, alcohol consumption also increased the abundance of some of the gram-negative bacteria (i.e, Porphyromonadaceae and Alloprevotella ).…”
Section: Discussionsupporting
confidence: 93%
“…The accumulation of harmful substances such as alcohol leads to liver injury and promotes the secretion of bile acid into the intestinal tract by the liver, thereby regulating the activity of various metabolic reactions in the intestinal tract [2,4,5,13]. The change in the type and number of intestinal flora is an important factor leading to abnormal liver function [20]. Liver disease can also lead to overgrowth and imbalance of intestinal flora [5,17].…”
Section: Discussionmentioning
confidence: 99%